Subjetividade, arte e educação na obra tardia de Herbert Marcuse - Baroni, Vivian (2014)
In this thesis we seek from an analytic stance reconstructive bibliographic-oriented character by a dialectical gaze, addressing the afterthought of Herbert Marcuse situated in the period of 1960-1970, trying to cover his analysis regarding the proposed theme: subjectivity, art and education. Try to question how the incorporation of the concept of reason repressive civilization, focuses on the constitution of subjectivity of individuals, and to analyze how the revaluation of artistic dimension, embedded in a program of aesthetic education, make it possible to rethink the concept of repressive reason and a possible qualitative human development based on the redefinition of culture. Because of dialectical negativity in this true work of art, cultural education fosters the development of critical thinking, that in the effort to overcome the immediate data, results in formation that creates restlessness and yearning for change. For this purpose, our research will be carried out through the development of three steps. Initially, we address the Marcuse analysis of society and culture, which rests on the concept of reason. We then analyze the role of the aesthetic dimension in Marcuse's later work, emphasizing the possible politicization of the subjective and artistic dimension. And finally, to demonstrate how a program of re-culturing, consolidating itself in the form of an aesthetic education could transform the repressive concept of reason. In this perspective, we consider very important change in the paradigm of reason prevailing in contemporary society, including the recovery of imagination and artistic dimension not only as valid forms of rationality, but also as guiding elements of transformation both in the subjective sphere as the objective existence of subjects. Thus, for real change to take effect, subjectivity should be of a political character, which could only be achieved through a critical education, based on the negative movement of the aesthetic dimension